Current Research on Methamphetamine-Induced Neurotoxicity: Animal Models of Monoamine Disruption - Taizo Kita; George C. Wagner; Toshikatsu Nakashima (Elsevier, 2003)
Methamphetamine (METH)-induced neurotoxicity is characterized by a long-lasting depletion of striatal dopamine (DA) and serotonin as well as damage to striatal dopaminergic and serotonergic nerve terminals. Several hypotheses regarding the mechanism underlying METH-induced neurotoxicity have been proposed. In particular, it is thought that endogenous DA in the striatum may play an important role in mediating METH-induced neuronal damage. This hypothesis is based on the observation of free radical formation and oxidative stress produced by auto-oxidation of DA consequent to its displacement from synaptic vesicles to cytoplasm. In addition, METH-induced neurotoxicity may be linked to the glutamate and nitric oxide systems within the striatum. Moreover, using knockout mice lacking the DA transporter, the vesicular monoamine transporter 2, c-fos, or nitric oxide synthetase, it was determined that these factors may be connected in some way to METH-induced neurotoxicity. Finally a role for apoptosis in METH-induced neurotoxicity has also been established including evidence of protection of bcl-2, expression of p53 protein, and terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL), activity of caspase-3. The neuronal damage induced by METH may reflect neurological disorders such as autism and Parkinson's disease.